Imagining Iraq Literature in English and the Iraq Invasion - Gupta, Suman; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
In the run-up to, during and after the invasion of Iraq a large number of literary texts addressing that context were produced, circulated and viewed as taking a position for or against the invasion, or contributing political insights. This book provides an in-depth survey of such texts to examine what they reveal about the condition of literature.
Keywords: British literature; Literature, Modern—20th century; Ethnology—Middle East .; America—Literatures.; Culture—Study and teaching; Literature—Philosophy.; British and Irish Literature; Twentieth-Century Literature; Middle Eastern Culture; North American Literature; Cultural and Media Studies, general; Literary Theory